The Blue Flame - Cantwell, Christopher (Vault Comics, 2023)
Repairman. Vigilante. Cosmic Hero. The Blue Flame is a cosmic hero. The Blue Flame is a DIY vigilante that fights crime on the streets of Milwaukee. The Blue Flame is a blue collar HVAC repairman named Sam Brausam. In the wake of a horrific tragedy, the boundaries of the Blue Flame's identity blur even further. Now, before a universal trial, the Blue Flame must prove that humanity is worth saving. But in order to do that, Sam Brausam has to save himself. Can he? An odyssey for answers at the heart of the universe.